2020
DOI: 10.3389/fnut.2020.580504
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact Potential of Supplemental Nutrients as Adjuncts of Therapy in High-Risk COVID-19 for Obese Patients

Abstract: The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) disease (COVID-19) in China at the end of 2019 caused a major global pandemic and continues to be an unresolved global health crisis. The supportive care interventions for reducing the severity of symptoms along with participation in clinical trials of investigational treatments are the mainstay of COVID-19 management because there is no effective standard therapy for COVID-19. The comorbidity of COVID-19 rises in obese patients. Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 238 publications
(185 reference statements)
1
23
0
6
Order By: Relevance
“…Healthy nutrition is very important and anyway mistaken or unbalanced diet can be risk factor affecting development of virus pathogenesis. Several research groups have shown that malnutrition or obesity exacerbate COVID-19 disease [35][36][37][38][39]. Therefore, to increase immunity in case of SARS-CoV-2 infection, an optimal diet was recommended with the inclusion of all the necessary nutritional components, trace elements and vitamins [35,[39][40][41][42].…”
Section: Quantitate Evaluation Of Socioeconomic Factors and Progress mentioning
confidence: 99%
See 1 more Smart Citation
“…Healthy nutrition is very important and anyway mistaken or unbalanced diet can be risk factor affecting development of virus pathogenesis. Several research groups have shown that malnutrition or obesity exacerbate COVID-19 disease [35][36][37][38][39]. Therefore, to increase immunity in case of SARS-CoV-2 infection, an optimal diet was recommended with the inclusion of all the necessary nutritional components, trace elements and vitamins [35,[39][40][41][42].…”
Section: Quantitate Evaluation Of Socioeconomic Factors and Progress mentioning
confidence: 99%
“…More than a few scientific groups have investigated the effects of diet on COVID-19 disease progression and mortality in distinct nations [39,40,42,43,45,46,48]. Kontis and coauthors [27] investigated data from the first wave of pandemic in 21 industrial countries and shown that magnitude of mortality was heterogeneous in this group of patients.…”
Section: Nutrition Habits and Outcomes Of Virus Epidemic In Differentmentioning
confidence: 99%
“…prevention of covid 19 [17]. In 50_200 μg/day dosage no side effects were reported [18].…”
Section: Journal Of Endocrinology and Thyroid Researchmentioning
confidence: 92%
“…The potential for food products, as functional foods or nutraceutical extracts from foods, to alleviate or modify COVID-19 transmission, morbidity or mortality is an especially attractive hypothesis when vaccines are not available. In reviewing the literature, the topic is replete with articles hypothesizing a beneficial effect of a healthy diet in reducing the incidence of COVID-19 infection and depressing its clinical symptoms [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. These articles review past association of a variety of nutritional factors that may influence infections in general and hypothesize that these same associations may modify COVID-19 viral morbidity and mortality.…”
Section: Nutrition As a Strategy For Coronavirus Disease 2019 (Covid-mentioning
confidence: 99%